The Tradition of the Reciting Al-Qur'an in the Great Mosque of Bandung - B. Busaeri (Indonesian Journal of Islamic Studies, 2018)
Tadarusan in the Great Mosque of Bandung is held every month of Ramadan, which is from the first Ramadhan to the end of Ramadhan, by completing 30 Juz, so that every day 1 juz. The author is interested in increasing the awareness of the Al-Qur'an regarding the phenomenon of the Koran Al-Qur’an and the purpose of the Al-Quran at the Bandung Grand Mosque, using Edmund Husserl’s phenomenologies approach with the first two steps of the epoche and the second eiditich vision. The results of this study indicate that people flocked to tadadrusan different stripes of different backgrounds there are housewives, employees, fathers, youth and children, who have a variety of different reasons there are those who answer because invited, fill in the blanks of time, take care of children, and there are those who want to expect a reward from reading the Qur’an. So the existence of the Al-Qur’an tadarusan is to broadcast or even read Al-Qur’an, so that people know and want to read the Qur’an regardless of the motive of the dilator behind it.